Factors influencing caster board skill acquisition - Suzuki, Hiroo; Hirakawa, Takehito; Yamamoto, Yuji (Frontiers in Psychology, 2025)
In motor learning research, various whole-body movement tasks have been examined using a dynamical systems approach. Prior studies have highlighted that differences in learning strategies and variability in movement contribute to individual differences in motor learning. Building on these findings, this study investigated the learning process of seven beginners as they attempted to ride a caster board for the first time and progressed until they were able to stand and ride it. Specifically, we aimed to compare and contrast commonalities and differences in the learning process to identify the factors contributing to individual differences and to clarify the motor skills crucial for mastering the caster board. To quantify movement changes associated with learning, we analyzed the initial velocity of the board and the amplitude of trunk rotational movement. Trial-by-trial changes were calculated to determine which variable exhibited greater change for each participant. Across all the participants, both initial velocity and trunk rotational movement increased with practice. These findings suggest that accelerating the board's initial velocity, which enhances stability, and increasing the amplitude of trunk rotational movement, which generates propulsive force, are both critical for mastering the caster board riding. However, the number of trials required to achieve the learning task varied by more than 100 trials across participants, and individual differences were also evident in the movement patterns at task completion. Case-based analyses revealed that these differences were influenced by the movement patterns performed in the early trials and by the variability in movement patterns executed across trials.